Investigation of delay tolerant network routing protocols with energy consumption analysis - Alusta, Farhat M. H. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Delay Tolerant Networks (DTNs) are the results of the evolutions in mobile networks in which an end-to-end path may not exist. The main principle of DTN to route messages is store, carry and forward technique, where intermediate hosts store data to be transmitted until it finds an appropriate relay host to forward the message in the route towards its target. DTNs have numerous applications in ad-hoc networking such as life monitoring and crisis management. Several routing and forwarding protocols have been proposed among the past few years. Majority of them uses asynchronous message passing scheme. The primary difference between various DTN routing protocols is the amount of knowledge that they have available to route the message. Flooding protocols such as Epidemic and Spray and Wait (SaW) routing protocols do not use any information. Predictive protocols such as PRoPHET and MaxProp uses past encounters of hosts to expect their future suitability to transmit messages to its destination. Store, carry and forward technique of DTN routing protocols causes a lot of copies of a message in the networks which consuming hosts’ resources like energy and buffer. The main challenge in DTN routing is how to increase delivery ratio of messages and consume less resources. This thesis focuses on the routing issue in DTNs using limited resources and investigate the performance of four well-known DTN protocols which is Epidemic, PRoPHET, MaxProp and SaW with the metrics node’s average remaining energy, number of dead nodes, delivery ratio, average latency and overhead ratio using the Opportunistic Network Environment (ONE) simulator. It has been observed that the performance of routing protocols has been affected by the changing of message generation interval, number of nodes, node’s speed, buffer size, time to live and the message size. The simulation investigation results that the SaW protocol outperforms other protocols in terms of energy consumption whereas MaxProp protocol has the highest delivery ratio. In contrast, Epidemic results the worst performance.

ÖZ: Gecikme Toleranslı Ağlar (DTN’ler), uçtan uca bir yolun mevcut olamayacağı mobil ağlardaki gelişmelerin bir sonucudur. İletileri yönlendirmek için DTN’nin esas ilkesi, depolanan taşıma ve iletme tekniğidir. Burada ara bilgisayarlar, iletiyi hedefe doğru bir rota içinde iletmek için uygun bir geçiş bilgisayarı bulana kadar iletilecek verileri depolar. DTN, yaşamı izleme ve kriz yönetimi gibi özel ağlarda çok sayıda uygulamaya sahiptir. Geçtiğimiz birkaç yıl içerisinde çeşitli yönlendirme ve iletme protokolleri önerildi. Çoğunluğu asenkron mesaj geçme şemasını kullanıyor. DTN yönlendirme protokolleri arasındaki temel farklılık, iletiyi yönlendirmek için kullanabilecekleri bilgi miktarıdır. Epidemic ve Sprey and Wait (SaW) yönlendirme protokolleri gibi taşan protokoller herhangi bir bilgi kullanmaz. PRoPHET ve MaxProp gibi öngörülen protokoller, gelecekteki uygun varış noktalarına ileti göndermek için bilgisayarların geçmiş karşılaşmalarını kullanır. DTN yönlendirme protokollerinin depolama, taşıma ve iletme tekniği, makinelerin enerji ve bellek gibi kaynaklarını tüketen mesajın birden fazla kopyasının üretilmesine neden olur. DTN yönlendirmesindeki ana zorluk, iletilerin dağıtım oranını nasıl artıracağı ve daha az kaynak tüketeceğidir. Bu tez, sınırlı kaynakları kullanan DTN’deki yönlendirme sorununa odaklanmakta ve düğümün ortalama kalan enerjisi, ölü düğüm sayısı, teslimat oranı, ortalama gecikme ve tepegöz oranı gibi ölçü birimleri, Opportunistic Network Environment (ONE) simülatörü kullanarak göstermektedir. Sonuçlardan yönlendirme protokollerinin performansının, ileti oluşturma aralığı, düğüm sayısı, düğümün hızı, arabellek boyutu, yaşama süresi ve ileti boyutunun değiştirilmesinden etkilendiği gözlemlendi. Benzetim çalışmaları, SaW protokolünün diğer protokollerden enerji tüketimi açısından daha iyi performans gösterdiğini, buna karşılık MaxProp protokolünün en yüksek teslim oranına sahip olduğunu gösterdi. Bunun yanında Epidemic protokolü en kötü performansı sergiledi.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2018. Co-Supervisor: Assoc. Prof. Dr. Ali Hakan Ulusoy, Supervisor: Assoc. Prof. Dr. Gürcü Öz
Keywords: Computer Engineering; Computer networks--Routing (Computer network management); Routing Protocols; Delay Tolerant Networks; Opportunistic Network Environment; Performance Evaluation; Energy Consumption Analysis